Detection and monitoring of the fauna of medium and large mammals using camera traps in a forest remnant area in the municipality of Água Fria de Goiás, Brazil – A tool for nature conservation (Research, Society and Development, 2024)
Despite the growing amount of information available, biodiversity is still under threat. Wildlife plays a crucial role in maintaining the ecological balance, and it is of logical and strategic importance to promote the further development of fauna recording and monitoring processes, emphasizing the need to strengthen the relationship between humans and nature. The aim was to record the species of medium and large mammals using camera traps. The study was conducted in the EcoCerrado Reserve in the municipality of Água Fria de Goiás, Brazil, between December 2020 and December 2022, using two camera traps in three different phytophysiognomies. 17 mammal species were recorded in 149 camera trap records, including species in the threatened category, such as Myrmecophaga tridactyla, Tapirus terrestrials, Chrysocyon brachyurus, Lycalopex vetulus, Panthera onca and Alouatta caraya. The mammal fauna observed in the study shows that this ecosystem can support populations of native species even in a modified landscape. This finding strengthens the basis for future initiatives aimed at environmental education, ecotourism, and more comprehensive legal protection for this region and other remnants of native vegetation in the Cerrado.